EFFECT OF WHEAT FLOUR AND LOW TEMPERATURE STORAGE TO SHELF LIFE AND SENSORY PROPERTIES OF PROBIOTIC SOY TEMPEH - Suharyono Suharyono; Samsul Rizal; Sussi Astuti; Raisa Amalia (Jurnal Agroindustri, 2019)
Tempe is one type of food that is easily damaged. The use of probiotic microorganisms in the preparation of tempeh is expected to increase the storability and quality of tempe sensory. This study aims to determine the effect of concentrations of wheat flour and low temperature storage that can extend shelf life and maintain the sensory properties of probiotic soybean tempeh. This study used a Complete Randomized Block Design (RCBD) with two factors and three replications. The first factor is the concentration of flour consisting of 5 levels (0%, 0.2%, 0.4%, 0.6%, and 0.8% (b / v). The second factor is the low temperature of storage, which consists from 3 levels (5 ° C, 10 ° C, and 15 ° C). Data obtained were analyzed descriptively for parameters of determination of shelf life, while parameter data of sensory properties (color, aroma, texture, and overall acceptance) were tested for their similarities with Barlett's test, the addition of data with the Tuckey test, and further testing with orthogonal polynomial test at the level of 5% and 1 %.The results showed that the shelf life of soybean tempe treated with probiotic microorganisms ranged from 12.33 to 17.33 days. orthogonal polynomials of wheat flour and low temperature storage have an effect on increasing color scores and texture, but have a significant effect on decreasing aroma score and overall acceptance.The best probiotic soybean tempe is obtained by adding 0.6% flour and 5 ° C storage temperature keep the shelf life of 17.33 days, color score of 3.72 (bright white), aroma score of 2.78 (somewhat typical of tempe and mildly sour), texture score of 4.12 (compact and solid), score equal to overall acceptance 3.41 (rather like), and the total lactic acid bacteria ranged from 9.04 log CFU / g to 9.13 log CFU /g